1999
DOI: 10.1080/00222349908248115
|View full text |Cite
|
Sign up to set email alerts
|

From microns to nanometers: Morphology development in semicrystalline polymers by scanning force microscopy

Abstract: In studies of spherulitic crystallization in polymers, many questions pertaining to the mechanism of the crystallization process have remained unanswered. A currently accepted view describes the development of spherulites from a framework of individual dominant lamellae that splay apart and branch (e.g., by a dislocation mechanism). This model, in addition, assumes that the space between the dominant lamellae is filled by subsidiary lamellae. In the center of a spherulitic entity, there is a hedritic core that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…Vancso et al [26] have determined the effect of a cantilever tip on the nucleation in poly(ethylene oxide) (PEO) thin film by using AFM. They demonstrated that a strong shear force on the PEO surface induced the nucleation parallel to the scanning direction by contact mode AFM tip.…”
Section: Lamellar Transition From Edge-on To Flat-on Orientationmentioning
confidence: 99%
“…Vancso et al [26] have determined the effect of a cantilever tip on the nucleation in poly(ethylene oxide) (PEO) thin film by using AFM. They demonstrated that a strong shear force on the PEO surface induced the nucleation parallel to the scanning direction by contact mode AFM tip.…”
Section: Lamellar Transition From Edge-on To Flat-on Orientationmentioning
confidence: 99%
“…The formation of chain-folded lamellae (i.e., primary nucleation) leads to further growth of the lamellae through the processes of branching and splaying (e.g., see Fig. 4 in Vancso et al 75 ). The degree of branching and splaying is mainly controlled by the degree of undercooling (i.e., the difference between the T m 0 and the T c : ⌬T ϭ T m 0 Ϫ T c ) in an increasing manner.…”
Section: Dependence Of Subsequent Melting Endotherms On Crystallizatimentioning
confidence: 99%
“…Pearce and Vancso [1,2] reported that the AFM tip could not induce poly(ethylene oxide) (PEO) crystallization. However, for poly(e-caprolactone) (PCL), Beekmans et al [3] observed the AFM-tip-induced nucleation of the PCL chains, which further resulted in the growth of edge-on crystals normal to the scan direction. The above two different results arise from their difference in strength of lateral forces applied in the AFM experiments.…”
Section: Introductionmentioning
confidence: 97%